1989
DOI: 10.1007/bf00026558
|View full text |Cite
|
Sign up to set email alerts
|

The determination of heavy metals in water, suspended materials and sediments from Langat River, Malaysia

Abstract: The distributions of heavy metals in the Langat River were studied for a period of six months between September 1984 and February 1985 . Heavy metals such as arsenic, cadmium, cerium, cobalt, chromium, caesium, lanthanum, rubidium, antimony, scandium, thorium and zinc were determined in water, suspended materials and sediment samples from the Langat River by neutron activation and atomic absorption spectrometry . The concentrations of arsenic, cadmium, cerium, cobalt, scandium, antimony, and zinc were generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…and 3.0-37.9 µg g −1 dry wt., respectively (Sarmani, 1989). In comparison with natural average global shale values (Mason and Moore, 1982), Pb in Juru River was about five times higher than natural values (20 µg g −1 ), while Cu was two times higher (shale value of 45 µg g −1 ) and Zn was four times higher (shale value of 95 µg g −1 ).…”
Section: Heavy Metals In Sedimentsmentioning
confidence: 96%
“…and 3.0-37.9 µg g −1 dry wt., respectively (Sarmani, 1989). In comparison with natural average global shale values (Mason and Moore, 1982), Pb in Juru River was about five times higher than natural values (20 µg g −1 ), while Cu was two times higher (shale value of 45 µg g −1 ) and Zn was four times higher (shale value of 95 µg g −1 ).…”
Section: Heavy Metals In Sedimentsmentioning
confidence: 96%
“…Yusuf [48] and Mamun et al [50] also investigated a similar concentration of Pb of 8.7 µg/L and 10 µg/L, respectively, in the Langat River (Table 3). However, Wang et al [58] recorded a very high Pb concentration of 154.96 ± 193.34 µg/L in the Huaihe River, China, whereas in Langat the highest concentration was recorded, 57.78 µg/L, mainly because of mining activities [49]. Sarmani [49] has reported very high concentrations of Cd (35.56 µg/L) and Pb (57.78 µg/L) in the Langat River, mainly because of water sampling near the mining sites.…”
Section: Water Quality Status In the Langat Rivermentioning
confidence: 96%
“…Mamun et al [50] also reported a similar concentration of dissolved Cd in the Langat River (1.0 µg/L). However, Sarmani [49] and Yusuf [48] have observed a very high concentration of Cd in the Langat River, 35.56 µg/L and 24 µg/L, respectively. Accordingly, Wang et al [58] investigated the highly dissolved Cd concentration of 61.74 ± 90.12 µg/L in the Huaihe River, China.…”
Section: Water Quality Status In the Langat Rivermentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Department of Environment of Malaysia (2009), Langat River is one of the most polluted rivers in the state of Selangor because of rapid industrialization and urbanization arising from infrastructural development and the expansion of the population. Chemical pollution has recently caused public concern regarding drinking water safety because the Langat River is the primary source of drinking water (Al-Odaini et al 2013;Azrina et al 2006;Lim et al 2013b;Sarmani 1989;Yusoff et al 2008). Continuous exposure to large amounts of sewage effluent from private and public sewage treatment plants, individual septic tanks, and domestic sewage can be one of the steroid hormone sources in the river water and sediment of the Langat River (Al-Odaini et al 2013).…”
Section: Introductionmentioning
confidence: 99%